Analysis of the efficiency of silicate clay on the control of Xanthomonas axonopodis PV. passiflorae in vitro and in seedlings of yellow passion fruit contaminated - Brancaglione, Priscila [UNESP]; Sampaio, Aloísio Costa [UNESP]; Fischer, Ivan Herman; Almeida, Aparecida Marques de; Fumis, Terezinha de Fátima [UNESP] (Soc Brasileira Fruticultura, 2009)
The bacterial spot in yellow passion fruit plants, caused by the bacteria Xanthomonas axonopodis pv. passiflorae, occurs in all producing areas of the country, and is responsible for great economic losses in the culture of passion fruit. This study aimed to test the efficiency of the silicate clay in the inhibition of the bacteria Xanthomonas axonopodis pv. passiflorae in vitro, and in both preventive and curative control of the bacterial spot in seedlings of yellow passion fruit plants. The silicate clay was added to the growth medium at concentrations of. 0.5, 1.0, 1.5 and 2.0%, placed in Petri dishes. After the culture medium was cooler, the bacterial suspension was inoculates (10(7) UFC.mL(-1)) with a handle, and left incubating at 28 degrees C for three days, and then the bacterial growth was evaluated. Subsequently, the product at the same concentrations above was sprayed on seedlings of 'Afruvec' passion fruit, as preventive or curative. The inoculation of the bacteria was made by foliar spraying of bacterial suspension (10(7) ufc.mL(-1)), 24 hours before or after the curative and preventive treatments, respectively. The severity of the disease was measured comparing each four true leaves from bottom up, with a diagrammatic scale. In the concentrations evaluated, the silicate clay inhibited both bacteria in vitro and symptoms of bacterial spot in the curative treatment. In preventive treatment, significant results were obtained using more than 1.0% of clay silicates. Based on these results, the clay silicate can be recommended, the concentration of 1.0-2.0% for the control of bacterial spot of passion fruit plants, in foliar sprays.
Keywords: Passiflora edulis; bacterial; management; silicon